Subaltern Women in The Novel Sing, Unburied, Sing by Jesmyn Ward - Muhammad Dandi Saputra; Muhd. Al-Hafizh (Universitas Negeri Padang, 2023)
This research is an analysis of the novel “Sing,Unburied,Sing